AB0415 Tendency to choose first biologic agent therapy of rheumatoid arthritis in the elderly: results from japanese multicenter registry. (15th June 2017) - Watanabe, T; Kojima, T; Takahashi, N; Asai, S; Asai, N; Matsumoto, T; Sobue, Y; Ishiguro, N
Abstract : Background: Of the treatment of rheumatoid arthritis (RA), biologic agent therapies are chosen, if disease activity remains moderate or high despite csDMARDs therapy. In the elderly, with comorbidity and their less spare ability, safety is often concerned in the choice of biologic agent. Objectives: We investigated the tendency to choose biologic agent and drug continuation rates in elderly in last decade. Methods: Records of relevant patients with RA were collected from the Tsurumai Biologic Communication Registry, wherein the department of Nagoya University and 20 affiliated hospitals in Japan are enrolled. A total of 873 biologics-naïve and age 65 and older patients were recruited from January 2004 to December 2014. We studied the choice of the biologic agent year by, and baseline disease activity and concomitant methotrexate (MTX) among TNF inhibiters, tocilizumab (TCZ), and abatacept (ABT) groups. Drug continuation rates were compared among TNF inhibiters, TCZ, and ABT groups. Results: From 2005 to 2010, etanercept (ETN) was used the most (2007; 73.5%, 2009; 65.9%). After the advent of ABT, ABT was used the most (2011; 44.3%, 2014; 38.8%). Baseline disease activity slightly decreased as a whole (DAS28-CRP; 4.88 to 4.44). Despite baseline disease activity of TNF inhibitors group decreased (DAS28-CRP; 4.88 to 4.37), that of TCZ group increased (DAS28-CRP; 4.94 to 6.24). In 2011–2014, baseline disease activity of TCZ group (5.85) was higher than that of TNF inhibiters group (5.11) (p<0.05). Concomitant MTX rate and dose were lower in ABT group (40.2%, 7.6mg) than that of TNF inhibiters group (79.0%, 8.9mg). 2 years drug continuation rate due to all unfavorable causes; ABT group was 92.4%, better than that of TNF inhibitors 87.1% and TCZ 69.2% (p<0.05). 2 years drug continuation rate due to adverse events; TCZ group was 80. 8%, lower than that of TNF inhibitors 94.6% and ABT 96.2% (p<0.05). Conclusions: ETN was used most before the advent of ABT. After the advent of ABT, ABT was used most and ETN decreased. This selection was made for speculation that ABT is lower risk than other biological agents. Baseline disease activity slightly decreased showing that tight control management became also popular among elderly. In 2011–2014, concomitant MTX rate and dose were lower in ABT group, but 2 years drug continuation rate was the highest. Disclosure of Interest: None declared